The Existence and Urgency of Customary Land In West Sumatra Province - Yevendri Yevendri (Pelopor Publikasi Akademika, 2023)
Customary land is land that is collectively owned by the local indigenous community. The tradition of customary land ownership has become an integral part of culture and community life in West Sumatra, and plays an important role in maintaining ecological balance and realizing the social welfare of indigenous peoples. However, in recent years, the existence of customary land in West Sumatra has faced various challenges and threats. This research aims to analyze the existence and urgency of customary land in West Sumatra Province. This research uses qualitative research methods. Data collection techniques were carried out by exploring journals, books and other information relevant to the research. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the existence of customary land in West Sumatra Province is still quite strong. Customary land is still used by indigenous people for various purposes, such as housing, agriculture, and plantations. The urgency of customary land in West Sumatra Province can be seen from various aspects, including social, economic and ecological aspects